PEMAHAMAN TERHADAP BAHAYA SEKS BEBAS PADA PESERTA DIDIK KELAS XI SMK NEGERI 1 PONTIANAK - Pupun Tamara; Yuline, Yuline; Amallia Putri (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
This research aims to describe the understanding of the dangers of casual sex in class XI students at SMK Negeri 1 Pontianak. The form of research uses a study survey. The sample in this study was 42 class XI students taken using random sampling. The research method used is descriptive quantitative. Data collection using indirect communication techniques using closed questionnaires. Data analysis uses percentage correction. The results of the research show that understanding of the dangers of free sex in class XI students at SMK Negeri 1 Pontianak is 93.86% in the "High" category, which means that overall students understand the dangers of sex. Students already understand the dangers of free sex with percentage data of 93.02%. With this, students have completely avoided something that would happen if they carried out this act. the factors causing the lack of understanding of the dangers of free sex have been resolved with a percentage of 93.45% in the good category. Preventing the impact of a lack of understanding of the dangers of free sex with a percentage of 95.05%. Enter the good category. Based on the description above, in general, understanding of the dangers of free sex has been successfully carried out in class XI of SMK Negeri 1 Pontianak.